(3GdeYGdLI GdbVGFjI hGdSjGSjI ddEfMQGa GdJTQjYj (B:s (3OQGSI ebGQfI (B/s - (3YHO GdefYe YHO GdMejO EHQGgje TQas; (3jMji GdLeds; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI(B:s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2001)
(3JfGhdfG ef NdGd gPG GdHMK OQGSI ehVhY GdeYGdLI GdbVGFjI hGdSjGSI ddEfMQGa GdJTQjYj HEYJHGQg ef Cge GdehVhYGJ GdJj JeS Mbhb GdCaQGO hMQjGJge(B. (3hdbO MGhdfG ef NdGd gPg GdQSGdI GdELGHI Ydi YOI CSFdI (B: - (3GdChd eG gj GdCSS GdafjI ddEfMQGa aj GSJYeGd GdSdWI GdJTQjYjI?, GdKGfj eG gj GdCSS GdhGbYjI ddEfMQGa aj GSJYeGd GdSdWI GdJTQjYjI ?, GdKGdK eG gh ehba GdbGVj GdOSJhQi ef GdEfMQGa GdJTQjYj, hgd eGQS OhQg aj QbGHI gPG GdEfMQGa, hgd CUOQ BjI CMcGe UQjMI HYOe OSJhQjI GdJTQjYGJ GdefWhjI Ydi Pdc GdEfMQGa, GdQGHY gd GdQbGHI Ydi OSJhQjI GdbhGfjf QbGHI eTQhYjI Ce QbGHI edGFeI ?(B: (3GdNGeS eG gj VeGfGJ aYGdjI GdQbGHI Ydi OSJhQjI GdbhGfjf ?, hdbO befG HOQGSI gPG GdehVhY OQGSI ebGQfI Hjf GdbGfhf GdaQfSj hGdbGfhf GdeUQis
(3CWQhMI (B((3OcJhQGg(B)-(3LGeYI GdbGgQI(B-(3cdjI GdMbhb(B-(3bSe GdbGfhf GdYGe, (B2001 s
(3jTJed Ydi EQLGYGJ HjHdjhLQGajI(B: (3UaMI (B992-1033s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdYGes; (3YjH YOe GdGNJUGUs; (3YjH GdTcd hGdGLQGAGJs; (3NUGFU GdGfMQGa GdJTQjYis; (3GdZdW GdHjf aj GdJbOjQs; (3eaghe GdeUdMI GdYGeIs; (3QbGHI GdbGVi Ydi GdSdWI GdJbOjQjI ddeTQYs; (3GdOhQ GdeSjWQ ddHQdeGfs; (3caGdI Mb GdJbGVis; (3GSJbdGd GdbVGA GdOSJhQis; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdYGes